SAT0257 Update on The Juvenile Systemic Sclerosis Inception Cohort Project. Characteristics of The First 74 Patients at First Assessment. (15th July 2016) - Foeldvari, I.; Klotsche, J.; Kasapcopur, O.; Adrovic, A.; Terreri, M.T.; Stanevicha, V.; Katsikas, M.M.; Alexeeva, E.; Sztajnbok, F.; Cimaz, R.; Kostik, M.; Sifuentes-Giraldo, W.A.; et al.
Abstract : Background: Juvenile systemic sclerosis (jSSc) is an orphan autoimmune disease. Currently just retrospective data exist regarding evolvement of organ involvement. In the retrospective studies assessment of the organ involvement is not standardized. Our project is the first one, where prospectively and with a standardized assessment data of jSSc patients are collected. Objectives: to learn about the characteristics and evolvement of jSSc Methods: Patients with jSSc were recruited worldwide and were prospectively assessed, using the proposed standardized patient assessment protocol. Results: 26 centers from 17 countries applied to participate on the project. The assent and consent forms were translated into the local native languages. Up till now 74 patients were enrolled. Sixty (81%) of the 74 patients were female. The mean age of the onset of Raynaud symptomatic was 9.2 years (0.2 – 15.9). The mean age at the onset of the non-Raynaud symptomatic were 9, 7 years (0.3 -15.9). 56 (76%) of the 74 have diffuse subtype, 10 (14%) of them have an overlap symptomatic. At the time of the inclusion the mean modified Rodnan Skin Score was 16.0. ANA positive were 55/71 (77%), 24/70 (34%) of them were anti-Scl 70 positive and 3/42 (7%) was anticentromere positive. 43/74 (58%) had already capillary changes and 36/72 (50%) inactive ulcerations, 13/72 (18%) had active ulceration at the time of the inclusion. 38/74 (51%) had cardiopulmonary involvement, 19/38 (50%) of had signs of interstitial lung disease on imaging, 18/42 (43%) had FVC <80% and 12/21 (57%) had DLCO <80%. 6/38 (16%) patients had pulmonary hypertension. 5/74 (7%) had renal involvement. 26/74 (35%) had gastrointestinal involvement, and 23/26 (88%) of them esophageal involvement. 46/73 (63%) had musculoskeletal involvement. 2/74 (3%) showed neurologic involvement. The mean CHAQ score was 0.4 (0–2.5). Patient global disease activity on VAS (0–100) was 44.9 and disease damage 41.6. Physician global of disease activity on VAS (0–100) was 39.7 and physician global of disease damage was 34.6. Conclusions: The current recruitment data confirms that pediatric patients are different from the adult patients, there is a significantly higher proportion of diffuse subset patients with 81%. 14% of the patients have overlap features. Disclosure of Interest: None declared